2013
DOI: 10.1021/bi401132w
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characterization of the Manganese-Sensing Pneumococcal Surface Antigen Repressor from Streptococcus pneumoniae

Abstract: Transition metals, including manganese, are required for proper virulence and persistence of many pathogenic bacteria. In Streptococcus pneumoniae (Spn), manganese homeostasis is controlled by a high affinity Mn(II) uptake complex, PsaBCA, and a constitutively expressed efflux transporter, MntE. PsaBCA expression is transcriptionally regulated by the DtxR/MntR family metalloregulatory protein pneumococcal surface antigen repressor (PsaR) in Spn. Here, we present a comprehensive analysis of the metal and DNA-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 72 publications
2
47
0
Order By: Relevance
“…ScaR represses the expression of scaCBA in the presence of Mn 2ϩ . Biochemical studies of the S. gordonii and S. pneumoniae ScaR proteins have shown that ScaR is a homodimer and contains two metal-binding sites per protomer (85,86). In S. pneumoniae ScaR, Zn 2ϩ occupies site 1, and although it is required for activation, it keeps ScaR in an inactive state.…”
Section: One-component Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…ScaR represses the expression of scaCBA in the presence of Mn 2ϩ . Biochemical studies of the S. gordonii and S. pneumoniae ScaR proteins have shown that ScaR is a homodimer and contains two metal-binding sites per protomer (85,86). In S. pneumoniae ScaR, Zn 2ϩ occupies site 1, and although it is required for activation, it keeps ScaR in an inactive state.…”
Section: One-component Systemsmentioning
confidence: 99%
“…In S. pneumoniae ScaR, Zn 2ϩ occupies site 1, and although it is required for activation, it keeps ScaR in an inactive state. Activation of DNA-binding activity is accomplished only when Mn 2ϩ occupies the lower-affinity site 2 (85). Zn 2ϩ can also bind to site 2, resulting in ScaR having a low DNA-binding activity (85).…”
Section: One-component Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excess iron (Fe) is harmful due to its participation in Fenton chemistry, which produces a highly reactive hydroxyl radical that can damage biomolecules (4-7). Other transition metals, including Mn, Zn, cobalt (Co), nickel (Ni), and copper (Cu), become toxic at high concentrations partly because they compete for each other's cognate metal-binding sites in enzymes (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Regardless of the mechanism of metal toxicity, bacteria have evolved ways to minimize the deleterious impact of metal ion excess.…”
mentioning
confidence: 99%